2008
DOI: 10.1073/pnas.0708220105
|View full text |Cite
|
Sign up to set email alerts
|

B-cell receptor activation inhibits AID expression through calmodulin inhibition of E-proteins

Abstract: Upon encountering antigens, B-lymphocytes can adapt to produce a highly specific and potent antibody response. Somatic hypermutation, which introduces point mutations in the variable regions of antibody genes, can increase the affinity for antigen, and antibody effector functions can be altered by class switch recombination (CSR), which changes the expressed constant region exons. Activation-induced cytidine deaminase (AID) is the mutagenic antibody diversification enzyme that is essential for both somatic hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 35 publications
1
45
1
Order By: Relevance
“…Moreover, we show that the MEK/ERK and PI(3)K pathways coordinate in regulating Rag, and an additive effect in the induction or suppression of Rag is obtained when both pathways are specifically inhibited. There are many examples in which expression of genes is regulated through multiple pathways, including NF-kB (55), BCL-2 family proteins (56), and activationinduced cytidine deaminase (57), which in many cases function for tuning expression levels and/or balancing functional properties of the target genes. Thus, the BCR activates two independent pathways that coordinate for induction of Rag and for tuning its expression level in B lineage cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we show that the MEK/ERK and PI(3)K pathways coordinate in regulating Rag, and an additive effect in the induction or suppression of Rag is obtained when both pathways are specifically inhibited. There are many examples in which expression of genes is regulated through multiple pathways, including NF-kB (55), BCL-2 family proteins (56), and activationinduced cytidine deaminase (57), which in many cases function for tuning expression levels and/or balancing functional properties of the target genes. Thus, the BCR activates two independent pathways that coordinate for induction of Rag and for tuning its expression level in B lineage cells.…”
Section: Discussionmentioning
confidence: 99%
“…In similar findings, Jabara et al (44) demonstrated that inclusion of an anti-IgM Ab in B cell cultures stimulated with LPS and IL-4 inhibits IgG1 expression and secretion and that this inhibition is not due to either suppressed or delayed proliferation or increased apoptosis. In another example of this phenomenon, Hauser et al (45) found that addition of an anti-IgM Ab decreased AID protein levels by 73% 1 h after addition to a culture of B cells that had been previously stimulated for 48 h with LPS and IL-4. This reduction in protein was due to inhibition of AID mRNA transcription rather than degradation of existing AID protein.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK inhibitor PD98059, but not the protein kinase C inhibitor bisindolylmaleimide, blocked the reduction in CD19 mRNA (Supplemental Fig. 1C Previous studies showed that the main Ca 2+ -sensor protein CaM, when Ca 2+ loaded, can bind to and inhibit transcriptional activities of E2A transcription factors (5,7,9,14,16,17). The E2A proteins have important roles in the transcriptional regulatory network that promotes commitment to and differentiation of B cells (18,19).…”
Section: Bcr Signaling Reduces the Sensitivity Of The Bcrmentioning
confidence: 99%
“…3C) for the indicated times. The MSCV-IRES-GFP-based retroviruses encoding wild-type and CaM-resistant m8N47 mutant of the E12 splice form of mouse E2A were described previously (5). Retrovirus concentrated by centrifugation was added with 5 mg/ml polybrene to 0.5 3 10 6 purified B cells after activation with CD40L plus IL-4 for 14 h (Figs.…”
Section: Activation and Infection Of B Lymphocytes From Mouse Spleensmentioning
confidence: 99%
See 1 more Smart Citation